Accident Severity Analysis In Johor - Albert, *; Sudesh Nair, Baskara (INTI International University, 2020)
Road accident has been a common problem in Malaysia. Road accidents occurred due to various factors with different type of accident severities. This study analyzed the relationship between the accident severities and accident factors in Johor. Accident severities were analyzed using R software to develop regression models that capable of predicting the number of accidents as well as the accident severities by road type, time of occurrence, and road geometry. As for the severity, there were three levels of severities that were presented in this study which were death, major injuries and minor injuries. The results showed that the combination of the federal road with straight road which took place around 8 PM to 10 PM were the most critical combination that caused the highest chance of fatalities. It was also shown that there were high chances for a driver to suffer death from road traffic accident anytime in the 24 hours.